Cryptology and Network Security 9th International Conference, CANS 2010, Kuala Lumpur, Malaysia, December 12-14, 2010. Proceedings - Heng, Swee-Huay.; Wright, Rebecca N.; Goi, Bok-Min.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the 9th International Conference on Cryptology and Network Security, CANS 2010, held in Kuala Lumpur, Malaysia, in December 2010. The 21 revised full papers, presented together with abstracts of 2 invited talks, were carefully reviewed and selected from 64 submissions. The papers are organized in topical sections on block ciphers, wireless network security, hash functions, public key cryptography, secure mechanisms, cryptographic protocols, and anonymous credentials.
Block Ciphers -- Cryptanalysis of Reduced-Round MIBS Block Cipher -- Impossible Differential Cryptanalysis of ARIA Reduced to 7 Rounds -- An Algorithm Based Concurrent Error Detection Scheme for AES -- Invited Talk I -- Cryptography for Unconditionally Secure Message Transmission in Networks (Invited Talk) -- Wireless Network Security -- Performance and Security Aspects of Client-Side SSL/TLS Processing on Mobile Devices -- A Practical Cryptographic Denial of Service Attack against 802.11i TKIP and CCMP -- User Tracking Based on Behavioral Fingerprints -- Hash Functions -- On the Collision and Preimage Resistance of Certain Two-Call Hash Functions -- Integral Distinguishers of Some SHA-3 Candidates -- Near-Collisions on the Reduced-Round Compression Functions of Skein and BLAKE -- Public Key Cryptography -- Practical Algebraic Cryptanalysis for Dragon-Based Cryptosystems -- Generating Parameters for Algebraic Torus-Based Cryptosystems -- Analysis of the MQQ Public Key Cryptosystem -- Efficient Scalar Multiplications for Elliptic Curve Cryptosystems Using Mixed Coordinates Strategy and Direct Computations -- Invited Talk II -- Cryptography Meets Hardware: Selected Topics of Hardware-Based Cryptography (Invited Talk) -- Secure Mechanisms -- Towards a Cryptographic Treatment of Publish/Subscribe Systems -- STE3D-CAP: Stereoscopic 3D CAPTCHA -- TRIOB: A Trusted Virtual Computing Environment Based on Remote I/O Binding Mechanism -- Cryptographic Protocols -- Dynamic Group Key Exchange Revisited -- Towards Practical and Secure Coercion-Resistant Electronic Elections -- Anonymous Credentials -- Predicate Encryption with Partial Public Keys -- Anonymous Credential Schemes with Encrypted Attributes -- One Time Anonymous Certificate: X.509 Supporting Anonymity.
Keywords: Computer science; Computer Communication Networks; Data structures (Computer science).; Data encryption (Computer science).; Coding theory; Computational complexity; Algebra -- Data processing; Computer Science; Data Encryption; Computer Communication Networks; Discrete Mathematics in Computer Science; Coding and Information Theory; Data Structures, Cryptology and Information Theory; Symbolic and Algebraic Manipulation